Protocol: An efficacy randomized controlled trial of Reciprocal Reading in high schools. (2019) - Cockerill, Maria; Thurston, Allen; Taylor, Andy
Highlights: Protocol for an efficacy randomized controlled trial with 311 children in 14 high schools. The intervention aims to improve reading comprehension and overall literacy. The intervention is a teacher/teaching assistant delivered program for reading comprehension instruction. Abstract: This paper presents the research protocol for an efficacy randomized controlled trial of the Reciprocal Reading program in high schools. The program is a workforce development program that supports Teachers and Teaching Assistants develop and deliver targeted reading comprehension instruction to high school students aged 11–13. The protocol outlines a Level 2 exploratory randomized controlled trial research design to assess whether the program delivered over approximately 6 months improves reading outcomes, in a sample of 311 children from 14 schools in four English districts with high socio-economic disadvantage. The primary outcome measure for analysis is reading comprehension with secondary outcomes of overall literacy and reading accuracy. A process evaluation will measure fidelity to implementation and potential for scale-up.